2021
DOI: 10.1177/21501327211017007
|View full text |Cite
|
Sign up to set email alerts
|

An Adapted Online Family Medicine Training for House Officers Amid Covid-19 Pandemic in Egypt

Abstract: Introduction The COVID-19 pandemic is an unprecedented challenge to house officers training programs because of the safety measures. Objective This current study aimed to introduce the adaptation of family medicine training for house officers during COVID-19 pandemic and gauge their level of satisfaction with the training. Methods Unfortunately, more than one-fourth of the house officers attending the family medicine training turned out to be hospital-admitted or in obligatory home isolation. A time-sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
(18 reference statements)
0
0
1
Order By: Relevance
“…Unlike recently published studies, the most used online platform among the participants in our survey was Google Classroom, followed by Microsoft Teams. This finding contrasts with previous work where ZOOM was reported to be the most commonly used online platform (Al-Balas et al, 2020;Ahmed et al, 2021;Brar et al, 2021;Herr et al, 2021;Temash et al, 2021). Herr et al (2021) found that ZOOM was the most used platform among South Korean dental students (Herr et al, 2021).…”
Section: Discussioncontrasting
confidence: 96%
“…Unlike recently published studies, the most used online platform among the participants in our survey was Google Classroom, followed by Microsoft Teams. This finding contrasts with previous work where ZOOM was reported to be the most commonly used online platform (Al-Balas et al, 2020;Ahmed et al, 2021;Brar et al, 2021;Herr et al, 2021;Temash et al, 2021). Herr et al (2021) found that ZOOM was the most used platform among South Korean dental students (Herr et al, 2021).…”
Section: Discussioncontrasting
confidence: 96%